ANALISIS KESALAHAN SISWA DAN STRATEGI DALAM MEMAHAMI KEKONGRUENAN PADA PEMBELAJARAN GEOMETRI SISWA SEKOLAH MENENGAH: SYSTEMATIC LITERATURE REVIEW - Tarizka Ozzi Pratiwi; Rika Mulyati Mustika Sari (Universitas Bhinneka PGRI, 2025)
This study aims to explain how students' errors in understanding the concept of congruence and suitable strategies in solving these problems, one of which is by applying ethnomathematics. Data was collected using existing sources such as journals, books, and other researches to produce scientific information. The results showed several student errors in congruence including a lack of understanding of the congruence theorem, difficulty in processing mathematical images and symbols, and errors in the proof steps. Some research from the review shows that ethnomathematics can help students by providing learning experiences that are not only useful but also build connections between abstract concepts and cultural realities.